Non-Cash Payment System Innovation and Its Implications on Financial System Stability in Indonesia - Shabrina, Almira; Kurnia, Akhmad Syakir (Jurnal Dinamika Ekonomi Pembangunan, 2023)
This study examines the impact of non-cash payment innovations on Indonesia’s financial system stability from 2009 to 2019. As technological advancements reshape payment systems, they present both opportunities and risks to financial stability. By utilizing the Structural Vector Auto Regression (SVAR) method, the study finds that the shift towards cashless payments reduces M1, indicating a decrease in the money supply. Additionally, innovations in the payment system increase the velocity of money circulation, which tends to drive inflationary pressures. However, the inflationary effect of non-cash payment transactions diminishes over time. This research highlights the dual nature of non-cash payment instruments in influencing both financial stability and inflation dynamics.